Social Support During Reentry: Family, Mentor, Religious, Parole Officer, and Social Service Roles - Liu, Lin (Criminal justice and behavior, 2023)
Existing research on social support and reentry primarily focuses on a single dimension of support, such as family or community support. Informed by the social support perspective, this study assessed how combined support from family, mentors, religious groups, parole officers, and social service agencies influences reentry outcomes. Given that the social support one receives during reentry is time-variant rather than static, longitudinal multilevel modeling was employed to examine how temporal changes in social support were associated with temporal changes in recidivism and drug misuse among people on parole. Results indicated that simultaneous support from family, parole officers, and social service agencies exerted protective effects on reentry outcomes. However, community-based mentoring programs had no significant effect on recidivism, and religious and social service support increased substance misuse. Policy implications derived from this research are discussed to address the intersection of various sources of social support.